Tartar crusaders - Schwarz, Habie (Princeton : Films for the Humanities and Sciences [production company] ; Kuala Lumpur : Visual Resources [distributor], 1994)
This program explores Europe's initial to the Mongol onslaught, which was to presume it some form of divine retribution sent to punish a sinful world
Director for NHK, Tomohidae Terai ; executive producer for NHK, Takashi Inoue ; series producer, Robert Marshall
Narrator : Sean Barrett
Keywords: Mongols -- History; Christianity -- Mongolia -- Early works to 1800; Tatars